(untitled) (El-Wahat Journal for Research and Studies, 2026)
Technological development in all areas of life in general, and law in particular, has influenced the formulation of legal rules, including those related to the expression of will in concluding contracts. After the expression of will was traditionally done orally, in writing, or by sign, the methods of expressing will have multiplied with the multiplicity of means available to express it. This forced the legislator to amend laws at times, and enact new laws at other times, including the enforcement of the Electronic Signature and Electronic Transactions Law in an attempt to fill the gap left by the development in the field of contracting. This study aims to shed light on the most important effects that occurred as a result of the electronic transformation and analyze them by presenting the texts related to the expression of will in Iraqi legislation. In order to present the study comprehensively, we divided it into three sections. The first was devoted to explaining the forms of expressing the will in the electronic transformation. Then, in the second section, we explained the effect of the electronic transformation on acceptance. In the third, we presented the effect of the electronic transformation on acceptance, and we concluded the study with the results and recommendations.